Malim Belief System in The Toba Batak Community in Air Kulim Village, Bathin Solapan District, Bengkalis Regency - Rizky Metro Siallagan; Suharti; Mutia Kahanna (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research is entitled "Malim Belief System in the Toba Batak Community in Air Kulim Village, Bathin Solopan District, Bengkalis Regency". The aim of this research is to describe the historical background, as well as look at the forms of rituals contained in the malim belief system in Air Kulim Village. The theory used in this research is Victor Turner's ritual theory which explains rituals. The method used is qualitative research. The data collection techniques are field observation, in-depth interviews and documentation. The data analysis techniques used in this research are collecting data, reducing data, displaying data and drawing conclusions. The results of this research show that the presence of this malim belief system originated from the Batak people in the North Sumatra area, which was spread by King Sisingamangaraja. Then King Sisingamangaraja gave a mandate to Raja Mulia Naipospos to lead the malim belief and disseminate the malim belief system. Until now, the malim belief system has developed into several areas in Indonesia, one of which is Air Kulim Village. Through a husband and wife who initially came to Air Kulim Village to migrate looking for work. In the Malim belief system there are several rituals that they still carry out today, namely: ceremony mararisabtu, ceremony martutuaek, ceremony pasahat tondi, ceremony mardebata, ceremony mangan na paet, ceremony sipaha sada, ceremony sipaha lima. Some of these rituals are still carried out by adherents of the malim belief system in Air Kulim Village as a form of worship to Debata Mulajadi Nabolon.